Metabolic Syndrome in Lean vs Obese Polycystic Ovarian Syndrome (PCOS) Phenotype - Goyal, Navjyoti; Sharma, Sarita; Bhatia, Ruby; Gupta, Sumeet; Pai, Raghavendra (Scripta Medica, 2026)
Background/Aim: Polycystic ovarian syndrome (PCOS) is the most common metabolic, hormonal and endocrinological condition. Compared to lean, obese PCOS women are more likely to experience infertility, irregular menstruation, acanthosis and hirsutism. Aim of this study was to investigate the prevalence of metabolic syndrome in lean and obese PCOS patients as well as its correlation with age, body mass index (BMI) and obesity.Methods: The 450 research participants in the cross-sectional study visited the tertiary care hospital. The individuals were chosen using the updated Rotterdam criteria and then divided into lean and obese groups according to their BMI. Clinical, biochemical, anthropometric, metabolic and demographic information about the patients were assessed and compared.Results: The average age of obese patients was 29.8 ± 8.47 years, whereas the average age of lean patients was 24.8 ± 7.07 years. Obese PCOS individuals had significantly higher levels of all examined parameters, including age, height, weight, WHR, hip and waist circumferences and BMI. Obese people were significantly more likely than thin people to have clinical parameters such infertility, alopecia, hirsutism, acanthosis and irregular menstruation. When comparing biochemical parameters such total testosterone (TT), luteinising hormone (LH): follicle stimulating hormone (FSH) ratio, thyroid stimulating hormone (TSH), dehydroepiandrosterone sulphate (DHEAS), the fasting oral glucose tolerance test (OGTT) and blood pressure, there were significant differences between PCOS patients who were thin and obese. Compared to lean individuals, obese patients showed higher levels of the lipid profile (p < 0.001). Metabolic syndrome was far more common in obese PCOS patients than in lean ones.Conclusion: Study showed that both lean and obese persons might have metabolic syndrome. Consequently, all PCOS patients require monitoring for cardio-metabolic risk, irrespective of age, weight, or BMI.